FSKKP Postgraduate Day 2017 - Mazlina, Abdul Majid (2017)
FSKKP Postgraduate Day was successfully organized with two wonderful events: ‘FSKKP Poster Competition’ and ‘FSKKP Postgraduate Dinner. Both events were organized by the FSKKP Postgraduate Society.